COVID-19 vaccine trials with children: ethics pointers - Atuire, CA; Salas, SP; Wright, K; Ambe, JR; de Vries, J (BMJ Publishing Group, 2022)
As healthcare authorities around the world strive to get as many citizens as possible vaccinated against the SAR-CoV-2 virus, many countries have begun including children in the population groups to be vaccinated. Properly designed clinical trials involving children are important to ensure safety, efficacy, and dosage of therapies in (developing) children. Within the complex health, social, and political scenario of the ongoing pandemic, ethics committees and policy makers in low-income and middle-income settings need to consider additional ethical questions when called on to review phase III COVID-19 vaccine trials involving in children. We set out some of the ethical questions to keep in mind before, during, and after the implementation of phase III COVID-19 vaccine trials in limited resource settings. Specifically, we discuss and offer succinct answers to the following questions: How relevant will the trial vaccine be for the population participating in the trial? Should vaccines that have not been approved for use among adults be approved for use in trials with children? Which children should be involved in COVID-19 vaccine trials? What criteria of informed consent are to be adopted with minors? Placebo versus an existing already approved vaccine? What specific duties of ancillary care should be taken into consideration for COVID-19 vaccines especially in low-income and middle-income countries? The answers we offer are considerations that can serve as ‘things to think about’ when reviewing or implementing COVID-19 trials involving children in low-income settings.